(untitled) (Conversatoria Linguistica, 2019)
In her novel Nad Niemnem Eliza Orzeszkowa created the character of a young farmer, Jan Bohatyrowicz, a representative of the impoverished nobility. Taking a portrait of Jan the writer made use of special technique – showing him in the surrounding nature. The character is also presented in action. He is a clearly positive figure. He cultivates the basic ethical values in his life. He is honest and hard – working. In the descriptions of various elements which contribute to the complete picture of the character’s life, the writer made use of particular parts of speech (verbs, nouns, adjectives, adverbs, pronouns), conventional as well as occasional word combinations, and stylistic means (epithets, similes, metaphors, personifications, onomatopoeic words). Orzeszkowa individualized the language of the character, employing for that purpose Old Polish language features of lexicon and syntax. Jan’s language is rich in salutations, aphorisms, similes and deminutives. The young man cultivates the old customs and traditions. He sings the old folk songs. With the aid of systemic and extra–systemic linguistic means the novelist excellently made her character realistic.